Seed-mediated synthesis and photoelectric properties of selenium doped zinc oxide nanorods - Ari Sulistyo Rini,; Rati, Yolanda; Agustin, Miranti; Hamzah, Yanuar; Akrajas Ali Umar, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Pristine ZnO and selenium doped ZnO (Se-ZnO) nanorods were successfully synthesized using seed-mediated hydrothermal method. The growth solution of both pure and Se-doped ZnO nanorods employed zinc nitrate hexahydrate (ZNH) and hexamethylenetetramine (HMT) as a precursor and surfactant, respectively. As a dopant source, selenium salt solution was obtained by reacting selenium powder with sodium borohydride at low temperature. The as-prepared pure ZnO and Se-doped ZnO nanorods were characterized using field effect scanning electron microscopy (FESEM), X-ray diffraction (XRD), UV-Visible spectroscopy (UV-Vis), and Photoluminescence (PL) spectroscopy. FESEM images show that the geometric shape of Se-ZnO nanoparticles is nanorods with a hexagonal cross-section. The XRD pattern shows the diffraction peak of the sample at the angles of 2θ: 34.44°, 36.25° and 47.54° which represents the hkl plane of (002), (101) and (102), respectively. The crystalline size calculated from XRD data is found to be in the range of 35-42 nm. The UV-Vis spectrum shows that Se-ZnO nanorods strong absorption peaks appeared in the range of 300-380 nm for all samples. Se doping has slightly altered the band gap energy of pure ZnO nanorods around 0.01 eV. The peak of the photoluminescence spectra of the sample at 470 nm indicates the blue emission band.